Analisis Sentimen BRImo dan BCA Mobile Menggunakan Support Vector Machine dan Lexicon Based - Pratama, Muhamad Rizky; Ramadha, Yudhi Raymond; Komara, Mutiara Andayani (STMIK Banjarbaru, 2023)
Services available on mobile banking can make transactions and request financial information, such as checkimg balances, viewing account mutation history and the like even so, it is felt that there are still opinions and complaint submitted by users in the Play Store review column of the application. Based on these problems, sentimen analysis research was carried out on reviews of the BRImo and BCA Mobile applications on the Play Store as research objects using the Support Vector Machine and Lexicon Based classification algorithms. Based on this result, it is known that the BCA Mobile application has more negative sentiment than the BRImo application. The sentiment classification of application reviews in testing the Support Vector Machine and Lexicon Based on the BRImo application obtained 94% accuracy and, on the BCA, Mobile application the accuracy was 95%Keywords: Lexicon Based; Mobile Banking; Play Store; Sentiment Analysis; Support Vector MachineAbstrakLayanan yang ada pada mobile banking dapat melakukan transaksi dan meminta informasi keuangan, seperti memeriksa saldo, melihat riwayat mutasi rekening, dan sejenisnya. Meskipun demikian, dirasa masih terdapat pendapat dan keluhan yang disampaikan oleh pengguna pada kolom ulasan play store dari aplikasi tersebut. Berdasarkan permasalahan tersebut dilakukan penelitian analisis sentimen pada ulasan aplikasi BRImo dan BCA Mobile di Play Store sebagai objek penelitian menggunakan algoritma klasifikasi Support Vector Machine dan Lexicon Based. Berdasarkan hasil tersebut diketahui bahwa aplikasi BCA Mobile memiliki sentimen negatif yang lebih banyak dibandingkan aplikasi BRImo. Klasifikasi sentimen ulasan aplikasi dalam pengujian menggunakan Support Vector Machine pada aplikasi BRImo didapatkan accuracy 94%, Lalu pada aplikasi BCA Mobile accuracy 95%.Â